Kebijakan Pelayanan E-KTP - Taufiq, Nur; widodo, Joko; Hartono, Supri (JPAP: Jurnal Penelitian Administrasi Publik, 2019)
The quality of public service of making e-ID card is a form of public service needed by society as personal identity. In the context of making e-ID card in Rungkut District Office of Surabaya City still found the complaints of the community. These complaints include the timing of incorrect e-ID card making. The formulation of the problem in this research is "How is the quality of e-ID card service for the people in Rungkut Sub-district of Surabaya City". The purpose of this study is to find out how the quality of e-ID card service for the community in Rungkut Sub-district, Surabaya City. The method used in this research is descriptive method with qualitative approach. Technique of data collecting done by questioner to 60 respondents, observation, and document. Based on the result of research, it can be concluded that the quality of e-ID card making service in Rungkut District Office that get good value is service requirement, service procedure, fairness of cost, courtesy and friendliness, service announcement, complaint procedure, suggestion and input, employee response. Those who get less value are service time, cost match, service result, officer ability, responsibility officer, disciplinary officer.Keywords: E-ID Card Service, Quality of Service, QualitativeÂ